Utilización del Moodle como plataforma virtual en apoyo a la asignatura de informática básica, en el programa de contaduría en la CUC y la CIAC. (2007)
Research work, so that the student of Public Accounting, uses the virtual platform Moodle as a support to the subject of Basic Computer science. Due to the problems that appears at present in the absence of use of this tool on the part of the teachers and pupils for not being obligatory, little knowledge of the benefits that this one offers and low invested time on the part of the teachers; it becomes necessary to initiate the development of this project. There realized analysis and interpretation of the obtained results of the instruments of compilation of information, to the students, teachers, coordinators, who supported this pedagogic proposal